PENGEMBANGAN MODUL SIFAT KOLIGATIF LARUTAN BERBASIS INKUIRI TERBIMBING - Afrina, Resa (RC-INSTITUT, 2019)
Colligative properties of solution is one of the chemical material that is abstract and uses many calculations so that this material is considered difficult by students. But participants can understand the material if guided to build their knowledge by discovering their own concepts and placing students as subjects of learning. The one of learning model that can be used to study the colligative properties of the solution according to the material characteristics is a guided inquiry model. This study aims to develop a module of colligative properties of guided inquiry-based solutions integrated with experiments, as well as expressing the validity and practicality of the module. This study included research and development (R & D) using the 4-D development model (define, design, develop, and disseminate). The research instruments used were questionnaires in the form of validity and practical sheets. Based on the results of the validity test, the average kappa moment value was 0.88 with a very high validity category. The results of practicality tests by teachers and students were respectively 0.92 and 0.82 with very high practicality categories. Based on the results of the research that has been done, the module of the colligative nature of the integrated inquiry-based inquiry solution for the high school students produced is valid and practice.   Keywords: Colligative properties of solution, guide inqury, module, reseacrh and development (R&D)